Novelty in Arundinella (Arundinelleae, Panicoideae, Poaceae): Morphological and Molecular Evidences for a New Species from Sikkim Himalaya - Saha, Suparna; Banerjee, Arnab; D. Dwivedi, Mayank; Pradhan, Durga K.; Maity, Debabrata (Phytotaxa, 2024)
A new species Arundinella namprikensis in the genus Arundinella supported by both morphological and molecular evidences, from the mountains of Sikkim Himalaya is described and illustrated. This species maintains its uniqueness from morphologically allied species A. nepalensis and A. cochinchinensis by possessing smooth and glabrous rhizomes, glabrous culm node, 5–7-veined lower and upper glumes, bisexual lower floret and the lower lemma almost always with 7 veins. Phylogenetic analysis of nuclear ITS sequences strongly supported the distinctiveness of A. namprikensis by forming a well-defined clade within Arundinella with its accessions sufficiently away from its close relatives, A. nepalensis and A. cochinchinensis. Information on its phenology, habitat, distribution and additional specimens examined are provided.